Small Human Population Drastic Impact, as Inferred From Multi-Proxies of a Temporary Carpathian Lake - Moldovan, Oana Teodora; Miko, Ladislav; Panaiotu, Cristian; Roban, Relu-Dumitru; Gąsiorowski, Michał; Hercman, Helena; Orza, Răzvan; Kenesz, Marius; Mirea, Ionuț Cornel; Petculescu, Alexandru; Robu, Marius; Constantin, Silviu (Frontiers in Earth Science, 2022)
Over the last thousands of years, human impact led to significant changes in the landscape, with impacts on the environment and the functioning of the ecosystems. We assumed that even small human settlements developed around water bodies might have a substantial impact that surpass the natural cycles of climate change in an area, especially linked to forest cutting. We have chosen a temporary lake in the Romanian Carpathians, as temporary lakes are overlooked in paleoclimatic studies, although having a potential as hotspots for paleoenvironmental researches. Zăton Lake has exposed riverbank sediments dated with radioactive lead and optical stimulated luminescence techniques, analyzed for sediments and paleomagnetism, and sampled for fossil Oribatida mites. The results show that for the last 2,200 years, natural cycles of warm and cold periods changed the oribatid communities around the lake, with warmer cycles of rich fauna alternating with poor fauna during colder periods. However, in the last centuries, the increased human occupation in the area replaced the ecologically diverse fauna with eurytopic taxa, more similar to the colder periods of the environmental evolution around the lake. Even if the human occupation around the lake was negligible, probably of a few hundred to ~2,500 people as in the present, the impact on the area is drastic, with ecologically non-specific species becoming dominant. In conclusion, even small and temporary water bodies can contain unique and valuable information on past histories of climate change and human impacts. At regional scales, the combined effects of climate change and long-term human impacts in local areas can have deleterious effects on invertebrate species and communities.